Association between morphometric variables and nocturnal desaturation in sickle-cell anemia - Cristina Salles; Marcelo Bispo; Regina Terse Trindade-Ramos (Elsevier, 2014)
Objective: to evaluate associations between morphometric variables, cervical circumference (CC), and abdominal circumference (AC) with the presence of nocturnal desaturation in children and adolescents with sickle-cell anemia. Methods: all patients were submitted to baseline polysomnography, oral cavity measurements (maxillary intermolar distance, mandibular intermolar distance, and overjet), and CC and AC measurements. Results: a total of 85 patients were evaluated. A positive correlation was observed between the height/age Z-score and CC measurement (r = 0.233, p = 0.031). The presence of nocturnal desaturation was associated with CC (59.2± 9.3 vs. 67.5 ± 10.7, p = 0.006) and AC measurements (27.0 ± 2.0 vs. 29.0± 2.1, p = 0.028). There was a negative correlation between desaturation and maxillary intermolar distance (r = -0.365, p = 0.001) and mandibular intermolar distance (r = -0.233, p = 0.037). Conclusions: the morphometric variables of CC and AC may contribute to raise suspicion of nocturnal desaturation in children and adolescents with sickle-cell anemia. Resumo: Objetivo: avaliar associações entre variáveis morfométricas e circunferências cervical (CC) e abdominal (CA) com a presença de dessaturação noturna em crianças e adolescentes com anemia falciforme. Métodos: todos os pacientes foram submetidos à polissonografia basal, medidas da cavidade oral (distância intermolar da maxila, distância intermolar da mandíbula e overje), CC e CA. Resultados: foram avaliados 85 pacientes. Foi observada correlação positiva entre o escore Z altura/idade e a medida da circunferência cervical (r = 0,233 p = 0,031). A presença da dessaturação noturna associou-se com as medidas da circunferência cervical (59,2 + 9,3 vs 67,5 + 10,7; p = 0,006) e abdominal (27,0 + 2,0 vs 29,0 + 2,1; p = 0,028). Houve correlação negativa entre a dessaturação e a distância entre os segundos molares da maxila (r = - 0,365, p = 0,001) e da mandíbula (r = - 0,233, p = 0,037). Conclusões: as variáveis morfométricas e circunferências cervical e abdominal podem contribuir para a suspeita da dessaturação noturna em crianças e adolescentes com anemia falciforme. Keywords: Sickle-cell anemia, Desaturation, Maxilla, Mandible, Sleep apnea, Palavras-chave: Anemia falciforme, Dessaturação, Maxila, Mandíbula, Apneia do sono